TINGKAT PENERIMAAN SOSIAL KELOMPOK TANI TERHADAP HUTAN KEMASYARAKATAN DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Muhammad Halim Mulkarim; Hafizianor Hafizianor; Hamdani Fauzi (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to analyze level social acceptance agricultural groups in community forestry in Pelaihari District, Tanah Taut Regency. Data analysis used Sociall Acceptance Index (IPS) formula (Social Acceptability or SAI). The object of the research was the Business Work Agriculture Group in KarangTaruna Village, HarapanBersama Agriculture Group in Ambungan Village and Kariya Jaya Agricultural Group in Ambungan Village in Pelaihari District, TanahLaut Regency, South Kalimantan. The level social acceptance of agricultural groups to existence community forestry programs in Pelaihari Tanah Laut regency is classified as high classification when agricultural groups social acceptance index value of 80.20% where the calculation results are obtained from scores each element of agricultural groups social acceptance index such as attitudes, participation and value, that means community has a high level social acceptance of the community forestry program.Keywords: Social Forestry; Social acceptance; Community Forestry